Quality of life for adolescents - Meuleners, Lynn (Curtin University, 2001)
Assessments of quality of life (QOL) for adolescents have received relatively little attention in the literature. Although there is no consensus on the definition of adolescent QOL and what aspects should be measured, it is generally accepted that QOL is a multidimensional construct. Issues related to adolescent QOL bear special considerations since experiences of adolescents are substantially different from those of adults. The aim of this study is to provide a better understanding of adolescent QOL by assessing the impact of determinants of QOL over a six-month period. The study will also evaluate the measurement properties of the latent factors underlying adolescent OL based on a second-order confirmatory factor analysis. A recursive structural equation model is then proposed to determine the direction and magnitude of the interdependent effects among the latent factors. The Quality of Life Profile Adolescent Version (QOLPAV), a generic 54-item questionnaire was utilised. It was administered to 251 adolescents without a chronic condition and 112 adolescents with a chronic condition at baseline and the cohort of 204 adolescent without a chronic condition and 96 adolescents with a chronic condition a six months. Stratified sampling was used to recruit the adolescents from high schools in the Perth metropolitan area. Subjects were aged 10 to 19. A non-categorical approach was utilised to recruit adolescents with a chronic condition. To account for the hierarchical effects of the adolescents nested within schools multilevel modelling was undertaken to explore the potential determinants of adolescent QOL perceived in his/her life and the opportunities available were found to be significant predictors for adolescent QOL. However, as expected, health was rated poorer, with more sick days reported by chronically ill adolescents.The results of the second-order confirmatory factor analysis suggested that adolescent QOL may be measured by five underlying constructs namely social, environment, psychological, physical health, and opportunities for growth and development. interdependent relations among these constructs identified the environment factor as primary, exerting both direct and indirect effects on the other four factors. A multivariate analysis of variance (MANOVA) also revealed no difference between chronically ill and healthy adolescents in their perceptions of the five constructs. Multilevel longitudinal analysis was performed to explore and quantify the variations in QOL over the six-month period. Although a large proportion of the variation can be accounted for by the covariates perceptions of physical health, age, control and opportunities, 38% of the variability in QOL scores was actually due to time. Similar to the baseline results, there was again no significant difference in the overall QOL scores between chronic and non-chronic adolescents at six months. Health was again rated poorer, with more sick days reported by chronically ill adolescents. The majority of both groups reported a positive QOL. Only 1% of the adolescents (non-chronic) reported a problematic QOL at baseline, which increased to 2.5% (non-chronic) at six months. There was also no significant change between the baseline QOL scores and those at six months. However, the social, physical health and opportunities for growth and development composite factor scores showed a decrease for both groups over the six months. The findings indicated that adolescents with a chronic condition do not view themselves different from their healthy counterparts in terms of QOL. The study enhanced our understanding of the effects of the broader determinants of adolescent health through a QOL perspective.The perceptions that teachers, parents and health professionals have on the relative importance of different aspects of QOL for the adolescent with a chronic illness were separately explored using a three round Delphi study. The first round questionnaire identified the level of importance each of the three panels attached to sixteen aspects relating to QOL. Panelists were also encouraged to provide additional comments on why they felt a particular item was important to the chronically ill adolescent's QOL. In round two, panelists were asked to prioritise the items in order of importance whereas round three attempted to achieve consensus within each of the panels. Differences between and within each of the panels in the prioritisation of item importance in round one and round two were evident. However, consensus was achieved in round three for the prioritisation of very important items by the panel of teachers. Items identified by by all three panels as extremely important included the adolescent's attitude, and friendships with the same age group. Themes to emerge from the qualitative responses to the open-ended questions included the adolescent "not Wanting to be different" and the importance of a "positive attitude". The majority of the three panels also perceived the QOL for the adolescent with a chronic illness to be worse than their healthy counterparts.Panelists were also encouraged to provide additional comments on why they felt a particular item was important to the chronically ill adolescent's QOL. In round two, panelists were asked to prioritise the items in order of importance whereas round three attempted to achieve consensus within each of the panels. Differences between and within each of the panels in the prioritisation of item importance in round one and round two were evident. However, consensus was achieved in round three for the prioritisation of very important items by the panel of teachers. Items identified by by all three panels as extremely important included the adolescent's attitude, and friendships with the same age group. Themes to emerge from the qualitative responses to the open-ended questions included the adolescent "not Wanting to be different" and the importance of a "positive attitude". The majority of the three panels also perceived the QOL for the adolescent with a chronic illness to be worse than their healthy counterparts.